Comparative analysis of quranic recitation: investigating the “good pause” conditions among leading scholars - Halabi, Omaimah Abdulrahman (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to compare the prominent sources and scholars’ statements in this science (Pausing and beginning) in order to know the difference between the terms, and to highlight conditions of agreement and disagreement among scholars. The focus is, also, to uncover the most prominent terms and their meanings seen individually by the scholars whose books are under consideration in this study. The importance lies in revealing the literal meaning and uses of the term by ‘Pausing’ scholars, primarily Al-Dani in his book ‘Sufficient’ and the reasons behind his selection of the term, and how concordant or contradictory he is with five of ‘Stopping’ scholars. These aims are achieved through inductive study and analytical comparison. The study revealed that there were 32 issues pointed out in ‘Good Stopping’ and 6 issues in Al-Anbari. However, Al-Ashmuni ‘Beginning’. agreed Ther with e were 14 Al-Dani issues on 5 issues, Al-Omani on 4 and Al-Sajawandi and Ibn Al-Nahhas exclusive to Al-Dani and 18 issues where he agreed with on one issue, while comparing Al-Dani with the five well-known books on ‘Good Pause’, it appeared that they were in agreement on (denotation) but in disagreement on (connotation).